Dampak Kepemimpinan Transformasional terhadap Inovasi Organisasi: Studi Kasus pada Perusahaan Teknologi - Puta, Taufan Eka; Arifin, Arifin; Arfah, Hj Aryati (SEIKO : Journal of Management & Business, 2024)
This study aims to investigate the relationship between democratic leadership styles and employee performance through case studies in the work environment. The research method used is a qualitative approach with data collection through in-depth interviews and participatory observation in an organization. The collected data are analyzed descriptively and interpretively to describe and analyze the relationship between the democratic leadership style applied by organizational leaders and employee performance. The results showed that democratic leadership style has a significant influence on employee performance in the work environment. Democratic leadership that involves employee participation and collaboration in decision-making has a positive impact on employee motivation, creativity, and engagement in work. Employees feel more valued and have a sense of belonging to organizational goals, which ultimately drives better performance. In addition, the study also revealed that factors such as open communication, support in skills development, and appreciation for employee contributions are important elements in shaping the relationship between democratic leadership styles and employee performance. This leadership style allows for the creation of an inclusive and collaborative work environment, where employees feel empowered and directed towards achieving better results. The conclusion of this study is that democratic leadership style has an important role in improving employee performance in the work environment. Organizations and leaders need to understand that the application of democratic leadership principles can provide tangible benefits in creating a positive work culture and increasing employee productivity and satisfaction. This research provides deeper insights into how democratic leadership styles can be integrated in management practices to drive organizational growth and success. Keywords: Democratic Leadership Style, Employee Performance, Case Study, Work Environment, Participation, Motivation